Informal Security Groups as Social Non-Movement in Indonesia: Case of Buru Jejak in Central Lombok - Permana, Yogi Setya (UI Scholars Hub, 2016)
This essay discusses vigilante groups in relation to access for rights to security, particularly in Central Lombok District, West Nusa Tenggara Province. Vigilante groups are defined as 'informal security groups' to distinguish them from formal security entities owned by the state such as the police and military. I propose an alternative interpretation toward the existence of informal security groups that is different from mainstream explanation. Most of the literatures have a strong tendency to categorize informal security groups merely as antagonist actors and a predatory element in the process of democratization in Indonesia. By referencing Asef Bayat’s notion of social non-movement, I argue that informal security group, in Lombok particularly, is one way ordinary people seek to improve their quality of life when security and access to justice are not available, resulting in a blurred line between legal and illegal activity. However, these groups are susceptible to be used by the local elites to achieve particular political interests. This research used qualitative methods, including interviews and archival research.